Assessment of Electric Propulsion Application in Light Rail Transit (LRT) - Lestari, Meiyanne; Kamar, Syamsul; Lamma, Mustari; Nugroho, Sinung (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
In this paper, one of the most important parts of self-propelled vehicles is presented, namely the Light Rail Transit (LRT), especially the propulsion system. LRT is already operating in several major cities in the world, but in Indonesia its construction has just been completed and is currently operating in Palembang, South Sumatra, and Greater Jakarta area (Jakarta-Bogor-Depok-Bekasi). The methodology used to describe and analyse the LRT propulsion system begins by first reviewing the literature on the development of LRT-type mass transportation in developed countries, then a study of technological developments is carried out on each component of the propulsion system, especially for the propulsion of rail facilities. One of the main components of the LRT-type rail propulsion system that will be used and developed in Indonesia is the VVVF inverter, which functions to regulate the speed of the traction motor which is designed to work in a certain frequency range, for example between 0 Hz to 70 Hz. The VVVF inverter output is controlled by a very popular principle used in railways, namely the constant V/f setting technique. The initial start of the LRT requires high torque to overcome train resistance and to accelerate in a few minutes. To meet these needs while still paying attention to energy savings, the traction power (traction effort) is adjusted, which is the power needed to move the train from a speed of 0 km/hour to 30 km/hour. Traction power is adjusted by varying the frequency to control the speed, the terminal voltage is also varied so that the ratio of the constant V/f constant is maintained at 15.7 V/Hz. The maximum torque of the motor becomes constant at every speed change.